2018
DOI: 10.1177/0363546518786480
|View full text |Cite
|
Sign up to set email alerts
|

Time Required to Achieve Minimal Clinically Important Difference and Substantial Clinical Benefit After Arthroscopic Treatment of Femoroacetabular Impingement

Abstract: At least half of patients treated with hip arthroscopy for FAI achieve MCID and SCB within the first 6 months after the procedure. However, clinically significant outcome improvement continues to be attained until 2 years postoperatively. Female patients, younger individuals, and those without chondral defects achieve faster clinical outcome improvement. These findings can be helpful for establishing shared decision-making aids and follow-up guidelines for arthroscopic treatment of FAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 17 publications
3
101
1
Order By: Relevance
“…1 Clinical researchers are beginning to explore the role and psychometric properties of outcome measures such as minimal clinically important difference (MCID), substantial clinical benefit (SCB), and patient acceptable symptomatic state (PASS). [2][3][4][5][6][7][8] Specifically, within the field of hip preservation surgery, a lot of attention has been paid to defining and understanding these clinical measures. In the study by Kivlan, Martin, Christoforetti, Wolff, Nho, Salvo, Ellis, Van Thiel, Matsuda, and Carreira 9 entitled "The Patient Acceptable Symptomatic State of the 12-Item International Hip Outcome Tool at 1-Year Follow-Up of Hip-Preservation Surgery," the authors sought to determine the PASS for the iHOT-12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Clinical researchers are beginning to explore the role and psychometric properties of outcome measures such as minimal clinically important difference (MCID), substantial clinical benefit (SCB), and patient acceptable symptomatic state (PASS). [2][3][4][5][6][7][8] Specifically, within the field of hip preservation surgery, a lot of attention has been paid to defining and understanding these clinical measures. In the study by Kivlan, Martin, Christoforetti, Wolff, Nho, Salvo, Ellis, Van Thiel, Matsuda, and Carreira 9 entitled "The Patient Acceptable Symptomatic State of the 12-Item International Hip Outcome Tool at 1-Year Follow-Up of Hip-Preservation Surgery," the authors sought to determine the PASS for the iHOT-12.…”
mentioning
confidence: 99%
“…Based on this delineation, prior work has proposed that MCID be considered a minimum target and lower bound of outcome improvement and SCB be considered the upper bound and optimal target. 2,5 Based on this definition, the authors misclassify SCB by stating: "The SCB differs from the PASS score in that it represents a change in score that distinguishes a subject as feeling 'normal' versus 'abnormal.'" I contend that SCB is not normal and represents an excellent (THE best) outcome.…”
mentioning
confidence: 99%
“…The previously reported MCID using the mean change method for the mHHS was 8, 18 and a net change of 11.31 was reported as slightly improved by Nwachukwu et al 29 When we considered the mean change in PROM scores in the current study to represent the MCID, we found a change of 15.2 for the mHHS and 20.7 for the SF-36. Given that our cohort consisted of all competitive athletes, a higher value for the MCID might have been expected; however, as the preoperative baseline PROM scores were generally much higher than in similar nonathletic cohorts, 3,9,28,30,39 the scope for the increase in PROM scores was also lower.…”
Section: Discussionmentioning
confidence: 91%
“…This limitation in the MCID has previously been reported Terwee et al 38 reported 5 MCID values for the physical function subscale of the WOMAC when using 5 different MCID methods on the same study population. Clinically significant outcome improvement may continue beyond 2 years postoperatively, 28 and as such, establishing MCID standards at this time point may be more valuable.…”
Section: Discussionmentioning
confidence: 99%
“…While 67% of individuals reported MIC of more than ten points at 6-months post arthroscopy, the average iHOT33 score of 60/100 did not reflect optimal hip function. This trend of recovery as measured by PROMs has become widely reported [58,78,127,178,202,219] and may be at odds with patient expectations. The extent of likely recovery and the time taken to achieve should be more widely advertised to individuals considering arthroscopy to improve their hip pain and symptoms.…”
Section: Part D: Overall Discussion and Thesis Conclusion __________mentioning
confidence: 98%